2003
DOI: 10.1097/01.tp.0000093464.72920.7c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cytokine functions in graft rejection by gene expression profiles1

Abstract: Our results indicate that IFNgamma plays a distinct role in the modulation of gene expression that includes STAT4-independent mechanisms. Our study identifies eight genes (IL-1beta, IL-1RA, macrophage inflammatory protein-1beta, monocyte chemoattractant protein-1, CC-chemokine receptor (CCR)-1, CCR2, CCR5, and F4/80) that are highly expressed in all of our experimental groups. Thus, these genes become candidates for essential functions during rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The initial development of antigen-specific cells into Th1 or Th2 phenotype and their stimulation by proinflammatory cytokines including IL-18 may be critical for the subsequent differentiation of inflammatory cells recruited specifically at the site of alloresponse [21]. Our data demonstrated upregulation of IL-18 production in patients with acute rejection of kidney allograft as compared to subjects with uncomplicated outcome or less advanced injury of kidney parenchyma manifested as acute tubulointerstitial nephropathy.…”
Section: Discussionmentioning
confidence: 50%
“…The initial development of antigen-specific cells into Th1 or Th2 phenotype and their stimulation by proinflammatory cytokines including IL-18 may be critical for the subsequent differentiation of inflammatory cells recruited specifically at the site of alloresponse [21]. Our data demonstrated upregulation of IL-18 production in patients with acute rejection of kidney allograft as compared to subjects with uncomplicated outcome or less advanced injury of kidney parenchyma manifested as acute tubulointerstitial nephropathy.…”
Section: Discussionmentioning
confidence: 50%
“…A recent study using a functional genomics approach with A␤-stimulated murine microglial cells identified cathepsin B as a key protein mediating microglial neurotoxicity [17]. In the present study, we report on gene expression changes in human microglia isolated from postmortem brain tissues, which were stimulated with aggregated/oligomeric A␤ and subjected to gene expression profiling using microarray hybridization analysis on oligonucleotide DNA arrays with content covering essentially all expressed human genes.…”
Section: Introductionmentioning
confidence: 94%
“…However, T1 implantation did not cause a significant increase in anti-Gal IgM and IgA levels in GGTA1 KO mice [17]. Therefore, G/i DKO mice may present a more sensitive model than the GGTA1 KO mice [34]. Our study showed IL-6 and IFN-γ expressions in the T1 group were significantly higher than those in T2 and control, indicating that IL-6 and IFN-γ could serve as sensitive indicators of immunogenicity of xenogeneic bone matrix.…”
Section: Discussionmentioning
confidence: 91%